2012
DOI: 10.1590/s0001-37652012005000043
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics prevent growth deficit of colon wall strata of malnourished rats post-lactation

Abstract: The objective of this study was to analyze morphometrically the colon wall strata of malnourished rats supplemented with probiotics. Sixteen recently weaned Wistar rats (Rattus norvegicus) were distributed into four groups: animals that received commercial chow (G1, n = 4); animals that received the same feed as G1 and were supplemented with probiotics (G2, n = 4); animals that received chow with 4% of proteins (G3, n = 4); animals that received the same feed as G3 and were supplemented with probiotics (G4, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Therefore, strategies to correct or reduce the damage caused by malnutrition must be investigated. Studies using probiotics have been performed for this purpose (Solis et al 2002, Cano et al 2002, Cano and Perdigón 2003, Dock et al 2004a, b, Dock-Nascimento et al 2007, Lima et al 2012. Probiotics are live microorganisms that when administered in appropriate amounts, are beneficial to the health of the host's organism (O'Sullivan and O'Morain 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, strategies to correct or reduce the damage caused by malnutrition must be investigated. Studies using probiotics have been performed for this purpose (Solis et al 2002, Cano et al 2002, Cano and Perdigón 2003, Dock et al 2004a, b, Dock-Nascimento et al 2007, Lima et al 2012. Probiotics are live microorganisms that when administered in appropriate amounts, are beneficial to the health of the host's organism (O'Sullivan and O'Morain 2000).…”
mentioning
confidence: 99%
“…Besides, the majority of them are restricted to describing alterations only of the mucosa (Allori et al 2000, Cano et al 2002, Dock et al 2004a, b, Dock-Nascimento et al 2007. Concerned with to entire wall strata from malnourished rats, Lima et al (2012) analyzed the large intestine and realized that the growth deficit of colon was prevented in animals treated with probiotics. But there are no investigations about the morphology of the different small intestine wall strata from malnourished rats treated with probiotics.…”
mentioning
confidence: 99%
“…Unfortunately the effects of different diets on the intestine morphology and also on its associated systems, such as endocrine and nervous systems, are almost unknown, despite some studies indicate that the microbial composition of mucosal communities in humans can be manipulated through the use of prebiotics (Langlands et al 2004).In this present volume two contributions evaluated the effects of severe protein malnutrition and the administration of probiotics on the digestive system of Wistar rats (Rattus norvegicus) (Sant`Ana et al 2012, Lima et al 2012. Sant`Ana et al (2012) specifically demonstrated that Wistar rats that received diets with severe protein restrictions display a reduction in the duodenum length, which is an interesting fact per se.…”
mentioning
confidence: 99%
“…However, the same authors also showed that a severe protein restriction diet could lead to the loss of specific neurons associated to digestive systems with an increase in the density of nitrergic neurons. The physiological effects of severe protein restrictions were clearly observed as the animals showed weight and fur loss, as well as diarrhea.Considering the effects of protein restriction on the digestive system development, Lima et al (2012) showed that Wistar rats that received a restrictive protein diet together with a probiotic culture did not present a growth deficit of the colon wall strata that generally occurs in malnourished rats especially after lactation. These data indicate that the administration of probiotics during the initial phases of the digestive system development seems to be important to drive the correct functionality of intestine, as also observed by other authors (Preidis et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation